Arts-based HIV and STI prevention intervention with Northern and Indigenous youth in the Northwest Territories: study protocol for a non-randomised cohort pilot study - Lys, Candice; Logie, Carmen H; MacNeill, Nancy; Loppie, Charlotte; Dias, Lisa V; Masching, Renée; Gesink, Dionne (BMJ Open, 2016)
Introduction Indigenous youth are disproportionately represented in new HIV infection rates in Canada. Current and historical contexts of colonisation and racism, disconnection from culture and land, as well as intergenerational trauma resulting from the legacy of residential schools are social drivers that elevate exposure to HIV among Indigenous peoples. Peer-education and arts-based interventions are increasingly used for HIV prevention with youth. Yet limited studies have evaluated longitudinal effects of arts-based approaches to HIV prevention with youth. The authors present a rationale and study protocol for an arts-based HIV prevention intervention with Northern and Indigenous youth in the Northwest Territories (NWT), Canada. Methods and analysis This is a multicentre non-randomised cohort pilot study using a pretest/post-test design with a 12-month follow-up. The target population is Northern and Indigenous youth in 18 communities in the NWT. The aim is to recruit 150 youth using venue-based sampling at secondary schools. Participants will be involved in an arts-based intervention, Fostering Open eXpression among Youth (FOXY). Participants will complete a pretest, post-test survey directly following the intervention, and a 12-month follow-up. The primary outcome is new or enhanced HIV knowledge, and secondary outcomes to include: new or enhanced sexually transmitted infections knowledge, and increased self-esteem, resilience, empowerment, safer sex self-efficacy and cultural connectedness. Mixed effects regression analyses will be conducted to evaluate pretest and post-test differences in outcome measurement scores. Ethics and dissemination This study has received approval from the HIV Research Ethics Board at the University of Toronto (REB: 31602). In addition, the project is currently registered in the NWT with the Aurora Research Institute (Licence: 15741). Trial results will be published according to the Transparent Reporting of Evaluations with Nonrandomised Designs statement. Trial registration ...